2018
DOI: 10.1159/000492931
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cognitive Impairment Affects Obstacle Negotiation in Older Adults: Results from “Gait and Brain Study”

Abstract: Background: Older adults with Mild Cognitive Impairment (MCI) are at higher risk of falls and injuries, but the underlying mechanism is poorly understood. Inappropriate anticipatory postural adjustments to overcome balance perturbations are affected by cognitive decline. However, it is unknown whether anticipatory gait control to avoid an obstacle is affected in MCI. Objective: Using the dual-task paradigm, we aim to assess whether gait control is affected during obstacle negotiation challenges in older adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 38 publications
(55 reference statements)
1
39
0
2
Order By: Relevance
“…These results were in line with some studies that have identified reduced gait speed as a predictor of preclinical stages of dementia or mild cognitive impairmetnt [23-25, 29, 30, 33-36]. Within the kinematic analysis of the walking speed, the coefficient of variation in the median walking speed, gait speed, gait variability as well as gait symmetry, specially in Dual Task conditions, were parameters which may be impaired in MCI Patients [62,63,[66][67][68] according to included studies of the present systematic review.…”
Section: Comparision With Other Studiessupporting
confidence: 90%
See 1 more Smart Citation
“…These results were in line with some studies that have identified reduced gait speed as a predictor of preclinical stages of dementia or mild cognitive impairmetnt [23-25, 29, 30, 33-36]. Within the kinematic analysis of the walking speed, the coefficient of variation in the median walking speed, gait speed, gait variability as well as gait symmetry, specially in Dual Task conditions, were parameters which may be impaired in MCI Patients [62,63,[66][67][68] according to included studies of the present systematic review.…”
Section: Comparision With Other Studiessupporting
confidence: 90%
“…The present systematic review establish that gait speed, especially on the dual task conditions [62,67,68], was signifi cantly reduced in subjects with mild cognitive impairment. These results were in line with some studies that have identified reduced gait speed as a predictor of preclinical stages of dementia or mild cognitive impairmetnt [23-25, 29, 30, 33-36].…”
Section: Comparision With Other Studiesmentioning
confidence: 56%
“…Whereas walking on curved paths is considered more difficult than that on straight paths, older adults with poor cognitive flexibility tend to exhibit risky walking behavior during more complex walking situations compared to older adults with good cognitive flexibility [40]. In this sense, deficits in higher-order cognitive processing may limit obstacle negotiation abilities in people with MCI, being a potential falls risk [41]. Based on these findings, and considering the third objective of the current study, the data showed that CGT performance was associated with EF (analyzed by PMT and TWT) and the number of falls in the preceding 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Higher‐level brain functions, which depend on cortical control, have been linked with less automatic controlled gait parameters or “nonrhythmic” gait parameters . These nonrhythmic parameters, including gait speed and stride‐to‐stride variability, subtly change during consciously anticipated upcoming balance threats while walking . On the other hand, lower‐level “locomotor centers” of gait control, located in midbrain and spinal regions, mainly regulate more automatic gait functions (“rhythmic” gait parameters) by rhythmically activating hip flexor muscles to generate legs' forward swing and step cadence .…”
mentioning
confidence: 99%
“…13 These nonrhythmic parameters, including gait speed and stride-to-stride variability, subtly change during consciously anticipated upcoming balance threats while walking. 14,15 On the other hand, lower-level "locomotor centers" of gait control, located in midbrain and spinal regions, mainly regulate more automatic gait functions ("rhythmic" gait parameters) 16,17 by rhythmically activating hip flexor muscles to generate legs' forward swing and step cadence. 18 Together, these studies provide evidence that different gait parameters are controlled by independent neural pathways.…”
mentioning
confidence: 99%